Susceptibility of rubber (Hevea brasiliensis) clones to Neofusicoccum ribis - A. I. C., Nyaka Ngobisa; M. A., Zainal Abidin; Wong, M. Y.; Nasehi, Abbas; Godswill, Ntsomboh Ntsefong; Pierre-Andre, Owona Ndongo (Science and Education Publishing, 2015)
The aim of this study was to evaluate the ability of Neofusicoccum ribis to infect leaf surfaces of different rubber (Hevea brasiliensis) clones. Neofusicoccum ribis isolates previously identified on the basis of morphological characteristics and DNA sequence analysis were used to inoculate rubber leaves and seedlings in vitro and in vivo respectively. Neofusicoccum ribis isolates were demonstrated to cause lesions on rubber clones examined in this study. There was variation in susceptibility of the rubber clones to the pathogen. This study provides useful information that could be exploited to better manage the disease.